Longitudinal associations between pain and cognitive decline in middle-aged and older Chinese adults: the mediating role of depressive symptoms - Cheng, Xia; Zhang, Kun; Liu, Jiayang; Hu, Jiaxin; Yuan, Qingxiu; Cai, Hang; Hu, Hongxia; Liao, Danfeng; Lin, Lin (Frontiers in Public Health, 2025)
ObjectiveThe primary aim of this scholarly investigation was to elucidate the correlation between Number of Pain Sites and cognitive decline within the older adult population. Additionally, the study sought to examine the potential mediating influence of depressive symptoms in moderating the association between pain and cognitive deterioration.MethodsWe analyzed 8,835 participants aged 45 and above, with data collected from 2011 to 2018. Participants were categorized into two groups—stable and rapidly declining cognitive function—using the KML3D clustering method. Binary logistic regression analysis was conducted to examine the association between pain status, depressive symptoms, and cognitive trajectories, and mediation analysis was used to assess the mediating role of depression.ResultsMulti-site pain was significantly associated with the risk of rapid cognitive decline (adjusted OR = 1.30, 95% CI: 1.14–1.48), and depressive symptoms were also a significant predictor of rapid cognitive decline (adjusted OR = 1.49, 95% CI: 1.32–1.68). Mediation analysis revealed that depression mediated the effect of pain on cognitive decline, accounting for 25.71% of the total effect.ConclusionOur study establishes a significant longitudinal link between Number of Pain Sites and cognitive decline, mediated in part by depressive symptoms. This finding underscores the need for interventions that address pain and depression to potentially decelerate cognitive decline in older adults.